Gas injection affects Marun field PVT properties - JAMSHIDNEZHAD, Mohammad (The Oil & gas journal, 2006)
A study determined the changes in pressure-volume-temperature (PVT) properties caused by gas injection in the Marun field Asmari carbonate reservoir in Iran. The study calibrated the equation-of-state models for compositional simulation and established a means for predicting fluid properties in all areas of the field. The study applied a Peng-Robinson equation of state (EOS)-based PVT program on the PVT data from samples collected before gas injection. A regression technique with dynamic parameter selection tuned the EOS to match these PVT data, after which the tuned Peng-Robinson EOS determined the PVT data from the wells sampled after gas injection. After gas injection, NISOC sampled from four wells and conducted PVT experiments on them. The results showed an average error of less than 6% and maximum error of about 7.79%.